DENSITOMETRIC VALIDATION OF LAPACHOL IN TECOMELLA UNDULATA SEEM BARK BY HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY - Richa, Raj; Nahida, Siddiqui; Vidhu, Aeri (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: To develop a validated high-performance thin layer chromatography (HPTLC) method for the quantitative estimation of Lapachol in a Soxhlet extracted bark of Tecomella undulata seem (T. undulata). Methods: The bark of T. undulata was extracted with chloroform by Soxhlet apparatus. The separation was achieved on a silica-gel 60 F254 HPTLC plate using toluene-ethyl acetateâ€“glacial acetic acid (8.5:1.5:0.02 v/v/v) as a mobile phase. Densitometric analysis of Lapachol was carried out in absorbance mode at 254 nm. Results: The proposed method was accurate for the separationÂ andÂ resolutionÂ betweenÂ peaksÂ of theÂ standard andÂ Lapachol (5.04Âµg) with RfÂ value 0.77. Calibration curves were found to be linear over the concentration range (10-130Âµg) for Lapachol and correlation coefficient over (R2= 0.9973), indicating an excellent correlation between peak areas and concentrations of the marker compound. The experimentally derived LOD and LOQ for Lapachol were determined to be 0.028 Âµg and 0.086 Âµg respectively and the developed HPTLC-UV method showed lower %RSD and SEM, value indicating the method to be precise, accurate and robust. Conclusion: The study concludes that HPTLC-UV validation method can be very efï¬cient and promising technique for the identiï¬cation and quantitative analysis of Lapachol from T. undulata bark. The statistical analysis of data indicates that the developed method is reproducible and specific.